The Moral Schizophrenia in the Fight Against Big Publisha - Al-Hoorie, Ali (Dutch Journal of Applied Linguistics, 2024)
In this contribution, Ali Al-Hoorie considers open science from a global South perspective and proposes a three-stage roadmap towards scholarship that is truly equitable.